The involvement and application potential of exosomes in breast cancer immunotherapy - Wang, Yun; Ma, Qiji; Wang, Tielin; Xing, Jie; Li, Qirong; Wang, Dongxu; Wang, Gang (Frontiers in Immunology, 2024)
Breast cancer has a high incidence and a heightened propensity for metastasis. The absence of precise targets for effective intervention makes it imperative to devise enhanced treatment strategies. Exosomes, characterized by a lipid bilayer and ranging in size from 30 to 150 nm, can be actively released by various cells, including those in tumors. Exosomes derived from distinct subsets of immune cells have been shown to modulate the immune microenvironment within tumors and influence breast cancer progression. In addition, tumor-derived exosomes have been shown to contribute to breast cancer development and progression and may become a new target for breast cancer immunotherapy. Tumor immunotherapy has become an option for managing tumors, and exosomes have become therapeutic vectors that can be used for various pathological conditions. Edited exosomes can be used as nanoscale drug delivery systems for breast cancer therapy, contributing to the remodeling of immunosuppressive tumor microenvironments and influencing the efficacy of immunotherapy. This review discusses the regulatory role of exosomes from different cells in breast cancer and the latest applications of exosomes as nanoscale drug delivery systems and immunotherapeutic agents in breast cancer, showing the development prospects of exosomes in the clinical treatment of breast cancer.